EDUKASI POLITIK PEMUDA KARANG TARUNA DESA LENTENG TIMUR DALAM MENGHADAPI PILKADA DI KABUPATEN SUMENEP - Nur Inna Alfiyah; Dwi Listia Rika Tini (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2021)
This service aims to provide education to youth groups in the youth group "Tunas Muda" in East Lenteng Village related to politics in order to face regional head elections that will be conducted by the Sumenep Regency government this year. Education is carried out through political education which later the knowledge and information obtained during education will be distributed to the community by youth youth. The implementation of this service uses the method of socialization and education in youth youth groups in Lenteng Timur Village. Education is carried out in this service through two activities namely related to how the role of youth youth in the electoral activity and organizational activity that later knowledge and information obtained during education will be distributed to the community by youth youth. This service is expected to be able to change the mindset of young people to the community towards their participation in politics.